Acute Alcohol Tissue Damage: Protective Properties of Betaine (Journal of Renal and Hepatic Disorders, 2021)
Teenage binge drinking is a major health issue; however, there is a paucity of data on liver injury. Herein, we investigated how acute ethanol affects juvenile hepatic cells through changes in oxidative stress, apoptosis, and liver function, as well as the ability of betaine, which can replenish the antioxidant glutathione and mitigate oxidative injury. Juvenile male Wistar rats were given either water or betaine (2% w/v) for 6 days and treated with either saline 0.15 mol/L NaCl or ethanol (75 mmol/kg body weight). After 24 h, liver enzymes, oxidative damage, apoptosis, and parameters of antioxidant enzyme activity were examined. Acute ethanol increased hepatic enzymes (99%, P < 0.05). Total protein and albumin levels were reduced by 14 and 18% (P < 0.001), respectively, which was prevented by betaine treatment. Cytosolic cytochrome c increased by 59% (P < 0.05), corresponding to a decrease in mitochondrial cytochrome c content, which was ameliorated with betaine. Cytosolic glutathione peroxidase was reduced with alcohol (P < 0.05) and was prevented with betaine. Subtle changes were observed in catalase, superoxide dismutase, glutathione reductase, and complex I activity after ethanol treatment. In summary, whilst juvenile animals appear to have higher basal levels of antioxidant enzymes, betaine conferred some protection against alcohol-induced oxidative stress.
Keywords: adolescents; antioxidants; binge drinking; liver; oxidative stress